Delay-aware cross-layer optimization method for FANET - Shaojie WEN; Chuanhe HUANG (Tongxin xuebao)
An asynchronous distributed cross-layer optimization (ADCO) method was proposed to solve the problem of jointly considering real-time routing,rate allocation and power control in FANET (flying ad hoc network).And a delay-constrained cross-layer optimization framework was designed to formally represent proposed problem.Then Lagrangian relaxation and dual decomposition methods was used to divide joint optimization problem into several sub-problems.ADCO allowed each relay node to perform the optimization operation for different sub-problems with local information,and the relay nodes could update the dual variables based on asynchronous update mechanism.The simulation results show that the proposed algorithm can improve the network performance effectively in terms of energy efficiency,packet timeout ratio and network throughput.